Ductal variant prostate carcinoma is associated with a significantly shorter metastasis-free survival. (May 2021) - Chow, Ken; Bedő, Justin; Ryan, Andrew; Agarwal, Dinesh; Bolton, Damien; Chan, Yee; Dundee, Philip; Frydenberg, Mark; Furrer, Marc A.; Goad, Jeremy; Gyomber, Dennis; Hanegbi, Uri; et al.
Abstract: Background: Ductal adenocarcinoma is an uncommon prostate cancer variant. Previous studies suggest that ductal variant histology may be associated with worse clinical outcomes, but these are difficult to interpret. To address this, we performed an international, multi-institutional study to describe the characteristics of ductal adenocarcinoma, particularly focussing on the effect of presence of ductal variant cancer on metastasis-free survival. Methods: Patients with ductal variant histology from two institutional databases who underwent radical prostatectomies were identified and compared with an independent acinar adenocarcinoma cohort. After propensity score matching, the effect of the presence of ductal adenocarcinoma on time to biochemical recurrence, initiation of salvage therapy and the development of metastatic disease was determined. Deep whole-exome sequencing was performed for selected cases (n = 8). Results: A total of 202 ductal adenocarcinoma and 2037 acinar adenocarcinoma cases were analysed. Survival analysis after matching demonstrated that patients with ductal variant histology had shorter salvage-free survival (8.1 versus 22.0 months, p = 0.03) and metastasis-free survival (6.7 versus 78.6 months, p < 0.0001). Ductal variant histology was consistently associated with RB1 loss, as well as copy number gains in TAP1, SLC4A2 and EHHADH . Conclusions: The presence of any ductal variant adenocarcinoma at the time of prostatectomy portends a worse clinical outcome than pure acinar cancers, with significantly shorter times to initiation of salvage therapies and the onset of metastatic disease. These features appear to be driven by uncoupling of chromosomal duplication from cell division, resulting in widespread copy number aberration with specific gain of genes implicated in treatment resistance. Highlights: Ductal adenocarcinoma of the prostate is more clinically aggressive than acinar adenocarcinoma. Ductal adenocarcinoma has shorter time to metastasis. This is the first large non-registry–based study to use metastasis-free survival as an end-point. RB1 loss may be a key molecular driver in clinical difference.